The effects of employee quotients on quality of life among smes in the Klang Valley - Kamaludin, Aqilah; Puteh, Fadilah (GADING Journal for the Social Sciences, 2024)
This study examines the effects of (i) emotional quotient, (ii) intelligence quotient, (iii) adversity quotient, (iv) spiritual quotient, and (v) social quotient on quality of life (QoL) among employees in small and medium-sized enterprises (SMEs) in the Klang Valley. Apart from exploring the impact of these quotients on employees' QoL, this study also aims to identify the key factors influencing QoL within this context. A quantitative methodology was employed to gather data from SME employees in the Klang Valley. The findings revealed positive and significant relationships between all five quotients and QoL among SME employees. However, the study highlights that emotional quotient and social quotient as the most influential factors, serving as the primary predictors of employee QoL. The research objectives were successfully achieved, shedding light on the interplay between emotional quotient, intelligence quotient, adversity quotient, spiritual quotient, social quotient, and QoL among SME employees in the Klang Valley. The outcomes of this study have practical implications for SME employees, providing insights to enhance their QoL by considering the various quotients explored in this study. By focusing on emotional and social quotients, organizations can develop targeted efforts to improve employee well-being and overall QoL. This study contributes to the understanding of factors influencing QoL within the SME sector and offers valuable guidance for enhancing employees' QoL in similar contexts.